PERSEPSI SISWA TERHADAP EFEKTIVITAS PEMBELAJARAN DARING - M Sholikun; Muhamad Khoirul Huda (IAI Al-Mawaddah Warrahmah Kolaka, 2023)
The Covid-19 pandemic some time ago was something that was never expected before, this pandemic has greatly affected the world of education. The education system underwent a change in the process of learning activities, from face-to-face learning to online learning. This study aims to determine how students perceive the effectiveness of online learning conducted at three Islamic Junior High School in Magelang. This study uses quantitative descriptive analysis with a sample of 210 respondents, from the Likert scale used the average respondent answered 3.56 points, it can be seen that students' perceptions of online learning some time ago were effective.